2022
DOI: 10.1186/s12913-021-07444-7
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for acute referrals to hospital from general practitioners and out-of-hours doctors in Norway: a registry-based observational study

Abstract: Background General practitioners (GPs) and out-of-hours (OOH) doctors are gatekeepers to acute hospital admissions in many healthcare systems. The aim of the present study was to investigate the whole range of reasons for acute referrals to somatic hospitals from GPs and OOH doctors and referral rates for the most common reasons. We wanted to explore the relationship between some common referral diagnoses and the discharge diagnosis, and associations with patient’s gender, age, and GP or OOH do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our study revealed the most common specific reason for referral as chest pain with 1,429 (16.3%) of all referrals made as a result of chest pain. A study conducted by Blinkenberg et al in 2022 also reported chest pain as one of the most frequent reasons for referral, forming 14,077 (5%) of all referrals [ 13 ]. However, their study has detected the most common referral cause as abdominal pain with 21.260 (8%).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed the most common specific reason for referral as chest pain with 1,429 (16.3%) of all referrals made as a result of chest pain. A study conducted by Blinkenberg et al in 2022 also reported chest pain as one of the most frequent reasons for referral, forming 14,077 (5%) of all referrals [ 13 ]. However, their study has detected the most common referral cause as abdominal pain with 21.260 (8%).…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome was hospitalization, defined as hospital admissions lasting for more than 24 h, 26 with a discharge diagnosis of acute sinusitis (ICD-10 code J01), intracranial infection, orbital infection, osteomyelitis or sepsis (all codes in Table S1 ), within 30 days after GP consultation. Hospital contacts labelled as follow-up or elective admissions were not included, and admissions were only included if there was no general practice contact with infections other than sinusitis between sinusitis diagnosis and admission.…”
Section: Methodsmentioning
confidence: 99%